The deep venous system of the lower extremity: new nomenclature - Kachlík, David; Pechacek, V; Musil, Vladimír; Báča, Václav (Phlebology, 2012)
The correct and precise nomenclature of the veins of the lower extremity is a necessary tool for communication. Three important changes have been done over the last 13 years. Terminologia Anatomica, the latest version of the Latin anatomical nomenclature, was published in 1998, extended in the area of the lower extremity veins with two consensus documents, in 2001, during the 14th World Congress of the International Union of Phlebology and in 2004 during the 21st World Congress of the International Union of Angiology. This article is a free continuation of two previous articles, reviewing the detailed anatomy and correct nomenclature of the superficial veins of the lower extremities and veins of pelvis. Now, it is concentrated on the deep venous system, in which 15 new terms have been added in both Latin and English languages.
Keywords: Lower Extremity; dolní končetina; kongresy jako téma; terminologie jako téma; vény; Terminology as Topic; Humans; Veins; Congresses as Topic; lidé